Influência da vegetação no conforto térmico do transeunte : estudo de caso em via com canteiro central em Vitória-ES - Ramaldes, Rosa Angela Casati (2015)
In urbanized areas of humid tropical climate the high temperatures often occur, the direct solar radiation in the urban surface materials generates heat gains that leverage the increased thermal value. The use of vegetation in cities can be a mechanism to